Project-Based Learning Evaluation from Students’ and Supervisors’ Perspectives: A Qualitative Research at Polytechnic Malaysia - Mustapha, Ramlee; M. Nasir, M. Ichsan; Sadrina, Sadrina (SCAD Independent, 2018)
The purpose of this case study was to evaluate the Project-Based Learning that was implemented at the Mechanical Engineering Department in a polytechnic in Malaysia. One kind of constructivism, Project-Based Learning was introduced into the Malaysian polytechnics curriculum regarding to result creative and innovative human resources. This study involved a random sample of 118 students and 43 supervisors in the Mechanical Engineering Department. The study found that both the students and supervisors agreed that Project-Based Learning approach is appropriate for the final project course J5012. In addition, both groups of respondents believed that the supervisors possesed adequate technical knowledge and implemented supervisory duties effectively. Nevertheless, students perceived the module content was hard to understand. The students barely agreed that the machines and equipments at the polytechnic were appropriate for the project. Positively, Polytechnic Kota Bharu should introduce a formal course of Project-Based Learning to the polytechnic system in Malaysia.